2019
DOI: 10.1111/evj.13076
|View full text |Cite
|
Sign up to set email alerts
|

Research trends in equine movement analysis, future opportunities and potential barriers in the digital age: A scoping review from 1978 to 2018

Abstract: Summary Background Since Muybridge's ‘horse in motion’, researchers in the equine movement analysis field continue to improve objective analysis and performance monitoring while ensuring representative data capture. However, subjective evaluation remains the primary method of equine gait analysis in the applied setting, despite evidence highlighting the unreliability of this approach. Objectives To map research trends, limitations and opportunities across the diverse equine gait analysis literature. Study desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 76 publications
0
32
0
Order By: Relevance
“…The introduction of sensor technology in motion studies allows easy collection of large amounts of high-resolution, high-sample rate data 8 that can be used to train models for gait classification. Here, we used sensor-based data to investigate the accuracy of different classification models, based on machine learning technology.…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of sensor technology in motion studies allows easy collection of large amounts of high-resolution, high-sample rate data 8 that can be used to train models for gait classification. Here, we used sensor-based data to investigate the accuracy of different classification models, based on machine learning technology.…”
Section: Introductionmentioning
confidence: 99%
“…There are currently three scoping reviews reported in the equine veterinary literature, all published between 2017–2019. These include a scoping review of equine movement/gait analysis [66], a scoping review of systematic reviews and meta-analyses for bovine and equine veterinarians [67], and a scoping review of acupuncture in companion animals [68].…”
Section: Discussionmentioning
confidence: 99%
“…These events can be examined visually but due to the limitations of the temporal resolution of the human eye [2] there are limitations to how well these events can be distinguished. Instead, objective measurement tools such as force plates, optical motion capture (OMC) systems and inertial measurement units (IMUs) are used [3].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, data collection is time consuming [4] and this method can only be used in a laboratory settings. In addition, multiple consecutive strides can only be measured with a force measuring treadmill and by force measuring shoes [3], which can alter the kinematics [5,6]. OMC systems and IMUs can also be used to measure consecutive strides and OMC systems are considered the gold standard for kinematic gait analysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation